The effect of level of dietary iron on pork muscle characteristics - Kropf, Donald H.; Mackintosh, D.L.; Hall, J.L.; Harrison, D.L.; Hunsader, M.; Ahlschwede, G.A. (Kansas Agricultural Experiment Station, 2011)
Muscle color is an important factor affecting shoppers’ choice of pre-packaged meats from self-service display cases. The effect of several levels of dietary iron and of two levels of a chelating agent on pork muscle characteristics was studied.
Keywords: Pork; Iron; Muscle color; Muscle characterisitcs